Integrating Digital Multilingual Literacy in the Merdeka Curriculum: A Case Study from Jambi Province - Siti Rahmiati; Viona Sapulette; Merlyn Rutumalessy; Hendra Sudarso; Everhard Markiano Solissa (Jurusan Teknik Informatika dan Komputer, 2025)
Digital transformation has significantly expanded opportunities for multilingual literacy in Indonesia, yet its integration within the Merdeka Curriculum at the junior high school level, especially in linguistically diverse regions such as Jambi Province, remains underexplored. This study aims to examine how digital-based multilingual literacy is implemented and to identify factors that facilitate or hinder its practice. A qualitative exploratory case study design was employed, involving five schools, three language teachers, one principal, and three students. Data were collected through in-depth interviews, classroom observations, and document analysis, and were thematically analyzed to capture pedagogical strategies, student experiences, and institutional support. Findings indicate that the Merdeka Curriculum enables the adaptation of national policies to local sociolinguistic contexts through translanguaging, digital storytelling, and collaborative learning strategies, enhancing student engagement, creativity, and communication skills. Challenges such as disparities in infrastructure, limited teacher training, and inconsistent policy application were observed, while active teacher agency, visionary school leadership, and community collaboration emerged as key factors sustaining innovation. Limitations include the restricted scope of research sites and the absence of quantitative evaluation of learning outcomes. Overall, the study concludes that integrating multilingual and digital literacy promotes inclusive and adaptive learning, strengthens students’ national identity, and fosters global competencies. Policy implications include the need for structured professional development, equitable allocation of digital resources, and participatory school governance to ensure the sustainability and scalability of multilingual-digital practices in Indonesian education.